Outcomes of SMMEs participation in incubator programmes in South Africa - Munnik, Daryn (Graduate School of Business (GSB), 2022)
South Africa's small, micro and medium enterprise (SMME) sector is an important contributor to GDP and employment. However, the contributions underperform the average low-income and middle-income country. The government has plans to increase SMME GDP and employment contributions. To do this, the Department of Small Business Development was recently established, and together with other agencies, several business incubators have been established. The number of incubators operating in the country has increased significantly in the recent past. There is a belief that incubators are organisations that will help SMMEs perform better and improve their chances of survival. To improve employment and GDP growth, SMMEs need to perform better and survive longer. However, there is limited evidence to confirm this understanding. This research aims to fill this gap of knowledge by investigating whether firms that participate in incubators have improved revenue, employment and financing performance, which improves survival prospects. The ordinary least squares estimation techniques was employed to estimate a cross sectional model to examine the effect of incubator participation on the performance of 182 SMMEs. The performance measures used included revenue, employment, and external equity, debt and philanthropic finance. The findings in the study from the cross-sectional analysis showed there was no selection bias and endogeneity evident. Firms with better performing dependent variables (revenue, employment and external financing) were no more likely to be selected to be incubated. Following this, the study found that firms that participated in incubators did not have a statistically significant different level of revenue, number of employees or external equity and debt financing, compared to firms that did not participate in incubators. The findings from the study indicated that increased participation in incubators did not guarantee increased revenue, employment and external equity and debt financing. The findings indicated that there was a possibility that incubated firms could raise more philanthropic financing than non-incubated firms. The policy recommendations from these finding are, therefore, to minimise the resources provided to incubators as they do not improve SMME performance. Resources should be provided to other SMME interventions such as providing growth capital directly to these firms.